Lymphocytic hypophysitis with central diabetes insipidus and consequent panhypopituitarism preceding a multifocal, intracranial germinoma in a prepubertal girl - Bettendorf, Markus; Fehn, Marita; Grulich-Henn, Jürgen; Selle, Barbara; Darge, K.; Lüdecke, D. K.; Heinrich, Udo; Saeger, W. (European journal of pediatrics, 1999)
We report the clinical course of a prepubertal girl with central diabetes insipidus (DI) and consequent panhypopituitarism evolving over a period of 10 years due to lymphocytic hypophysitis and subsequent germinoma. Two years after the diagnosis of central DI was established, MRI revealed a thickened pituitary stalk. Later pituitary enlargement and increasing thickening of the pituitary stalk impinging on the optic chiasm required a trans-sphenoidal biopsy which disclosed active hypophysitis with lymphocytic infiltrates and necrosis. High dose dexamethasone treatment only temporarily halted the disease process. Therefore, stereotactic radiation therapy was performed as a rescue treatment and MRI findings almost reversed. However, the subsequent MRI showed multiple intracranial lesions identified histologically as a germinoma and a standard chemotherapy and radiation was performed.
Gesehen am 15.12.2020